Implementasi Pendidikan Karakter melalui Budaya Sekolah di SMP Negeri 1 Teluk Keramat Kabupaten Sambas - Aldian Tomia; Syamsuri Syamsuri; Thomy Sastra Atmaja; Bistari Bistari; Shilmy Purnama (Departement of Mathematics Education, 2024)
The research aims to identify and describe the implementation of character education through the school culture at SMP Negeri 1 Teluk Keramat in Sambas Regency. The researcher employed a qualitative descriptive research approach. The study involved students, the vice-principal, and civics education teachers as informants. Data collection methods used in this research encompassed observations, interviews, and document analysis. Data analysis in this study encompassed data reduction, data presentation, and drawing conclusions. The findings of this study reveal that character education through the school culture at SMP Negeri 1 Teluk Keramat in Sambas Regency is executed via various routine, spontaneous, exemplary, and conditioning activities. Routine activities consist of flag-raising ceremonies, recitation of prayers before and after lessons, Quranic readings before lessons, Quranic recitation sessions, class monitoring duties, and